(untitled) (Annual of the Faculty of Philosophy in Skopje, 2023)
The purpose of this paper is aimed at examining the educational needs and didactic competences of teachers for the preparation and use of didactic-methodical teaching materials in the teaching of the subject Macedonian language for the program areas Initial reading and writing and Language (first, second and third grade), and all with the aim of improving the teaching of the Macedonian language. For the successful realization of the goals/standards for evaluation needed in the program areas Initial reading and writing and Language from the first to the third grade, it is necessary to prepare, apply and classify the teaching materials that will serve as a kind of teaching support for the teachers, but also for the students , which will help them in learning the Cyrillic and Latin letters, writing and reading with them, language and spelling rules, as well as the application of spelling signs. In teaching practice, there is a need for didactic-methodical design of teaching materials within the program areas Initial reading and writing and Language, respecting modern methodical, methodological and dokimological principles. For that reason, the examination of the attitudes and educational needs of teachers, as immediate implementers of teaching, is the methodological justification for their inclusion as a special research subsample.